Developmental venous anomaly associated with dural arteriovenous fistula: Etiopathogenesis and hemorrhagic risk - Agosti, Edoardo; De Maria, Lucio; Panciani, Pier Paolo; Serioli, Simona; Mardighian, Dikran; Fontanella, Marco Maria; Lanzino, Giuseppe (Frontiers in Surgery, 2023)
Introduction: Developmental venous anomalies (DVAs) have traditionally been defined as non-pathological congenital lesions. Compared to isolated DVAs, the association of DVAs with arteriovenous shunts seems to have a more adverse clinical connotation. In this review, we describe the association between DVA and dAVF and discuss the hemorrhagic risk. We also advance a hypothesis about the potential de novo formation of a DVA and challenge the dogma about their “developmental” or “congenital” nature. Methods: A systematic review of the literature on the association of DVA and dAVF was performed in accordance with the PRISMA-P (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols) guidelines. Results: A number of 678 papers was initially identified, but only 9 studies were included in the final qualitative analysis. Most of the patients presented with bleeding (56%), with a median GCS of 14 (range 10 – 15). In 56% of the cases the DVA had a supratentorial location. Supratentorial DVAs mostly drained in the superior sagittal sinus (80%), while all of infratentorial/combined DVAs drained in deep ependymal veins of the 4th ventricle. All the supratentorial dAVFs drained into the superior sagittal sinus, while the infratentorial/combined dAVFs mostly drained in the jugular bulb, Vein of Rosenthal, or transverse-sigmoid sinuses (75%). Most of the dAVFs were classified as Cognard type IIa+b (67%), while in a smaller number of cases type I (22%) and type V (11%). The dAVF was the target of treatment in each case and most patients underwent endovascular treatment (78%). The dAVF was completely occluded in 78% of cases and no periprocedural complications were reported. Conclusion: The clinical presentation, radiological findings, and treatment outcomes of DVAs and associated dAVFs have been discussed. Despite the general opinion that DVAs are benign congenital lesions, increasing epidemiological and radiological evidence supports a potential acquired origin, and the venous pathways seem to play a pivotal role in their post-natal genesis and development.